OPSB Services and Promotions Manually and Digitally as a Form of Learning Resource Center Innovation in the School Environment - Yunitha Ike Christyowati; Eva Relieffia; Sunah; Retno Danu Rusmawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
OPSB is an entity designed to facilitate students in utilizing learning resources, both individually and in groups. The research method used in this article is literature study or literature study. Digital promotions allow OPSB to reach a wider audience, conduct accurate targeting, and measure campaign performance better. A successful digital promotion strategy includes website optimization, content marketing, social media, online advertising, email marketing, data analysis, and flexibility that includes building superior OPSB services, promotion of the OPSB brand, and continuous adaptation to keep up with technological developments and trends market. Overall, this article underscores the importance of integrated services, promotions, and marketing strategies in OPSB to achieve sustainable business growth in the digital era.